Effect of solvent pretreatments on intraradicular bond strength of bioactive cements - Salim, Ikram Aqel; Salim, Anas Aaqel; Stape; Thiago Henrique Scarabello; Mutluay, Mustafa Murat; Tezvergil-Mutluay, Arzu (Elsevier BV, 2025)
Bioactive materials are gaining interest in dentistry due to their ability to interact with dental tissues promoting healing and regeneration; albeit their ability to bond to root dentin remains unclear. This study investigated the effect of solvent-containing pretreatments on intraradicular bond strengths of bioactive cements. Sound premolars were decoronated, root canals were instrumented and irrigated using sodium hypochlorite and water. Roots were randomly divided into eighteen groups (n = 7/group) based on dentin pretreatments (no treatment, dimethyl sulfoxide (DMSO), ethanol (EtOH), EtOH/H2O, DMSO/H2O and DMSO/EtOH) and bioactive cements; a light-curable calcium silicate (Theracal LC, Bisco, Chicago, Illinois, USA), a mineral trioxide aggregate (Orbis MTA, P.L. Superior Dental Materials GmbH, Hamburg, Germany), and an experimental surface pre-reacted glass ionomer root canal material (S-PRG, Shofu Inc, Higashiyama-ku, Kyoto, Japan). Root canals were filled with bioactive cements and stored for 7 days at 37 degrees C. Filled roots were sectioned perpendicular to their longitudinal axis to obtain 1-mm thick slices. Intraradicular bond strengths were measured by the push-out bond strength test (0.5 mm/min). Analysis of failure mode was performed using a stereomicroscope. Characterization of bonded interfaces was performed via SEM. Bond strength data was analyzed by Kruskal Wallis test and ANOVA on ranks (alpha = 0.05). Bond strengths varied according to bioactive cements, Theracal > MTA > S-PRG, and root thirds (p < 0.05). Aqueous (DMSO/H2O) or ethanolic (DMSO/EtOH) dilutions of DMSO increased Theracal bond strengths to apical root segments (p < 0.05). While MTA bond strengths were not affected by pretreatments, undiluted ethanol reduced bond strengths of S-PRG to apical root segments (p < 0.05). Intraradicular bonding of bioactive cements may vary according to root canal depth and material composition. Solvent-based pretreatments containing DMSO might improve intraradicular bonding of resin-modified bioactive cements in a concentration-dependent manner.